A pilot study on the feasibility of training nurses to formulate multicomponent oral health interventions in a residential aged care facility. (23rd August 2017) - Deutsch, Alan; Siegel, Emma; Cations, Monica; Wright, Clive; Naganathan, Vasi; Brodaty, Henry
Abstract : Objectives: This 10 weeks feasibility study investigated whether residential care nurses with 12 hours advanced oral health training in assessments and saliva testing could formulate, implement and monitor individualised oral care plans of early dementia residents. Method: Four trained lead advocate nurses using SXI‐D, OHIP14, oral health assessment tool (OHAT) assessments and a modified saliva test formulated nurse scheduled comprehensive oral care plans (NSCOCPs) by selecting and scheduling preventive products and procedures multiple times throughout the day to alkalise the mouth of 8 residents as an adjunct to assisted brushing and high‐fluoride toothpaste. Results: Nurse assessments, saliva tests and care plans were validated against oral health therapist (OHT) findings. Care plan agreement between Nurse and OHT intervention selection and scheduling was high (75%‐88%). Untrained nurse compliance was very high, 86%‐99% for the 4930 scheduled interventions. Untrained nurses delivered multiple scheduled interventions by following NSCOCPs despite initially not understanding the reason for each of 9 interventions categories. NSCOCPs could track and monitor whether a recommended intervention had been completed by general nursing staff over 3 nursing shifts. Conclusion: The role of nurses may have to be expanded beyond traditional roles to meet the growth and changes in oral health needs in residential facilities. Intensive training of a few lead advocate nurses to assess risk and formulate individualised NSCOCPs provides a method to transfer knowledge to untrained staff and deliver multicomponent preventive interventions soon after entry into residential care where timely visits by dental professionals to examine residents and prescribe preventive interventions are infrequent or unlikely.